Internal Supervision in Handling Domestic Violence by Police Members: The Role of Investigation Supervisory Officers from the Perspective of Accountability and Conflicts of Interest - Candra Ermala; Harmono Harmono (Jurnal Legisci, 2026)
Background. The handling of domestic violence cases involving police members presents complex problems, especially related to independence and accountability in the investigation process. On the one hand, the legal system has provided an adequate normative framework to ensure the professionalism of the authorities and the protection of victims. On the other hand, on-the-ground practice shows a tension between lawsuits and institutional dynamics that affect the effectiveness of internal oversight. Aims. This study aims to analyze the role of the Investigation Supervisory Officer (Wasidik) in supervising the handling of domestic violence cases by police members, examine the legal basis governing this role, and identify structural and cultural obstacles affecting its implementation. Methods. This study uses an empirical legal method with a socio-legal approach, which views law as a social practice shaped by institutional structures, organizational cultures, and power relations. Data were obtained through interviews with law enforcement officials as well as studies of relevant laws and regulations and scientific literature. The analysis is conducted qualitatively, integrating empirical findings and theoretical frameworks to understand the gap between legal norms and surveillance practices within police institutions. Result. The results of the study show that normatively internal supervision has been well structured through a formal mechanism, with Wasidik serving as the quality control for the investigation. However, in practice, the effectiveness of supervision is still influenced by structural factors such as a hierarchical bureaucratic system, as well as cultural factors such as corps solidarity and unbalanced power relations. Supervision tends to be oriented towards administrative compliance and institutional risk management, so it does not fully guarantee substantive justice for victims. In addition, transparency limitations affect the public's perception of supervisory independence. The novelty of this research lies in the affirmation that the main problem of internal supervision in domestic violence cases involving police members is not in the weakness of regulations, but in the dominance of organizational culture and the institutional logic that shapes supervision practices. Conclusion. Therefore, it is necessary to strengthen a supervisory model that is more responsive, transparent, and oriented towards victim protection through increasing the capacity of the apparatus, strengthening supervisory independence, and integrating external accountability mechanisms.